A study on factors that influencing customer loyalty towards Pahang State Farmers Association (PASFA)/ Norshamsiah Ibrahim - Ibrahim, Norshamsiah (Faculty of Business and Management, 2011)
This study is to investigate the factors that influencing the customer loyalty towards PASFA. PASFA had sell the agricultural product througout Pahang State. So, the first objective of this study is to study the factors that will influence the customer loyalty towards PASFA. The second objective is to determine the relationship between independent and dependent variables which are service product quality, service quality and price fairness and to determine the most influence dimension toward the customer loyalty . Descriptive research has been chosen as a research design and the method for data collection for this study is questionnaire. 170 questionnaires have been personally distributed to the at PAFA store who are currently buy the product from the PASFA store. The distribution process was taken all the operation hours which is from 8.00 a.m until 5.00p.m and from 21st March until 1st April 2011. The analysis of findings in this study consists of frequencies of demographic profile, , Reliability analysis, Pearson correlation and Multiple Linear Regression. Lastly is the conclusion and recommendation, researcher will determine which dimension that most contribute to the customer loyalty and the relationship between customer loyalty with product quality, servuce quality and orice fairness. The researcher will make the recommendations in this study based on the conclusion and observations.